PKM Peduli Lingkungan Guru SMPN Wonomulyo Melalui Cerpen Ekokritik - Juanda Juanda; Azis; Iswan Afandi (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2023)
Short stories are reading materials as literacy skills that contain a variety of environmental education. This Community Service aims to improve the skills of teachers, especially junior high school teachers in Wonomulyo District, to be skilled at choosing and downloading digital short stories with environmental themes; Teachers are skilled at determining the values of environmental education in digital short stories. The Service Team in carrying out this activity uses lecture training methods, discussions, workshops, and download tutorials and determines the values of environmental education in short stories. The partners in this Community Service were 15 teachers in junior high school, Wonomulyo District, Polman Regency, West Sulawesi Province. The results achieved are partners who are skilled at selecting and downloading digital short stories and skilled at determining the values of environmental education in short stories. The output of this PKM is in the form of news on the online media Barru Pos and YouTube videos.